A theoretical study on structures of neutral (CuS)n (n = 1–10) clusters and their interaction with Hg0. (1st August 2022) - Wang, Yahui; Huo, Qihuang; Fan, Hongjun; Wang, Jiancheng; Chang, Liping
Highlights: Most of the ground state structure of (CuS)n clusters are firstly reported. (CuS)n clusters, especially when n = 3–5, can interact with Hg 0 strongly. Hg atom acts similarly to Cu during the reaction between Hg 0 and (CuS)n clusters. Composite mercury sorbent of (CuS)n /graphene is modeled and tested theoretically. The specialty of CuS material in metals sulfides on mercury removal is explained. Abstract: In recent years, CuS materials, especially nanomaterials, were found to have outstanding performance in mercury removal, and were taken as a promising alternative to the traditional mercury sorbents. In this work the mercury removal mechanism of CuS nanomaterials was investigated theoretically. Firstly, the structures of (CuS)n (n = 1–10) clusters were revised, and quite a few new ground state structures were located. Then the adsorption of Hg on (CuS)n clusters and on graphene supported (CuS)n clusters were studied. Results show that the adsorptions of Hg 0 on clusters are stronger than those on the clean CuS (0 0 1) surfaces, which agrees with the fact that CuS nanoparticles perform better in mercury removal than CuS bulk. Furthermore, the mercury removal ability of (CuS)n cannot be destroyed by the introduction of graphene, in line with the excellent performance of CuS-modified carbon materials reported in experimental studies. It is found that Hg is adsorbed chemically on (CuS)n cluster, acting as Cu to expand the Cu-core, and further stabilized by the bridging S atoms. The specialty of CuS in various metal sulfides on mercury removal was discussed, and it is the mix-valence Cu 1+ /Cu 2+ and S 1- /S 2- in CuS that cause the coexistence of Hg-S and Hg-Cu interaction.